The Effect of Macroeconomic Fundamentals, Capital Structure, Financial Performance, and Company Size on Investment Decisions in Automotive Companies listed on the Indonesia Stock Exchange - Elmiano Artanto Epot Erong; Hwihanus Hwihanus (International Journal of Economics and Management Research, 2024)
This research aims to examine and analyze the influence of macro fundamentals of capital structure, financial performance and company size on investment decisions in automotive companies listed on the Indonesian Stock Exchange. The type of research carried out was quantitative with secondary data sources obtained from the Indonesian Stock Exchange. The population in this research is automotive companies listed on the Indonesia Stock Exchange, totaling 12 companies. This research uses SmartPLS. The results of this research show that macro fundamentals have a positive and significant influence on investment decisions, macro fundamentals have a positive and significant influence on financial performance, macro fundamentals have a negative and significant influence on capital structure, macro fundamentals have a negative and significant influence on company size, financial performance has a negative and significant influence on investment decisions, capital structure has a positive and significant effect on investment decisions, company size has a positive and significant effect on investment decisions.